THE ROLE OF FORENSIC ACCOUNTING AND ARTIFICIAL INTELLIGENCE TO UNCOVERING GREENWASHING PRACTICES IN SUSTAINABILITY REPORTS - Eka Adetya Finata; Andini Azarina; Meri Lisnawati; Hastanti Agustin Rahayu (Jurnal Akuntansi dan Ekonomi Bisnis, 2026)
This study aims to analyze the role of forensic accounting and artificial intelligence (AI) in detecting greenwashing practices using the Systematic Literature Review (SLR) approach. The study systematically reviews 15 scientific articles published between 2018 and 2025, collected from databases such as Google Scholar, DOAJ, and Research Gate, using predefined inclusion and exclusion criteria. The screening process was conducted through identification, filtering, and eligibility assessment to ensure the relevance and quality of the selected studies. The study examines previous research findings discussing the use of forensic accounting and AI in detecting indications of greenwashing, including the application of Natural Language Processing, machine learning, and text mining.